Pengukuran Beban Kerja Psikologis dan Fisiologis Pekerja di Industri Tekstil - Prima Fithri; Windi Fitri Anisa (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2017)
The development of manufacturing industries are growing rapidly along with the progress of time and the increasing sophistication of technology today, one of which is a manufacturing company engaged in the textile field is PT Unitex Tbk Bogor. PT Unitex Tbk Bogor is a company that processes raw materials into semi-finished and finished materials such as cotton processing up into yarn or fabric. The production process costs physiological and psychological workload which could harm an operator at each work station. The packing work station has the highest workload due to its heavy workload and worker fatigue. This study measures the psychological work load by employing NASA - TLX method. On the other side, for evaluating physiological workload, the pulse rate and body temperature of the operators are measured.